Age and growth of fishes of genus Haemulon ( Pisces Pomadasyidae ), in Ceará State, Brazil - Ximenes Carvalho, Maria Odete; Fonteles Filho, Antonio Adauto (Arquivos de Ciências do Mar, 2018)
In this paper an analysis is made of the length at age data for the white grunt, Haemulon plumieri, and the blue-striped grunt, H. melanurum populations that inhabit the tropical waters off Ceará State, Brazil, with the aim of calculating its growth curve and drawing comparisons with stocks from higher latitudes, in terms of growth rate and maximum asymptotic length. The da ta were obtained 1Jy backcalculation of sizes estimated from age rings in scales of individuais measuring from 13.5 to 32.1 em ( H. plumieri ) and 15.3 to 28.0 em ( H. melanurum ) in fork length. The growth equations are: L1 = 38.3 [ 1- exp (- 0.168 ( t + 2.1) ), for H. plumieri, and L1 = 31.3 [ 1- exp (- 0.315 ( t + 1.4) ), for H. melanurum. The white grunt population of Brazil (tropical waters) reaches a smaller L∞ (38.3 em ) but grows quicker ( K = 0.168) than that of the Uníted States ( temperate waters) which has a bigger L∞ ( 53.4 em ) and a lower growth coefficient (K = 0.108 ). These findings confirm the theory according to which as latitude increases, individual fish grow more slowly but live to attain a larger size.